Tri- (M=CuII) and hexanuclear (M=NiII, CoII) heterometallic coordination compounds with ferrocene monocarboxylate ligands: solid-state structures and thermogravimetric, electrochemical and magnetic properties - Müller, Karoline; Koo, Changhyun; Klingeler, Rüdiger (Polyhedron, 2017)
The synthesis and characterization of the hexanuclear [M2(κO-O2CFc)2(µ-O2CFc)2(µ-H2O)(κ2N,N′-tmeda)2] (MII=Ni, 5; Co, 6; Fc=ferrocenyl, (η5-C5H4)(η5-C5H5)Fe; tmeda=N,N,N′,N′-tetramethylethylendiamine) and the trinuclear [Cu(κ2N,N′-tmeda)(κ2O,O′-O2CFc)2 2] (7) coordination compounds are described. Compounds 5-7 were prepared by the consecutive reaction of ferrocene carboxylic acid (FcCO2H; 1) with [nBu4N]OH followed by treatment of in situ formed [nBu4N][FcCO2] with the metal salts [M(tmeda)(NO3)2] (M=Ni, 2; Co, 3; Cu, 4). The structures of 5-7 in the solid state were determined by single crystal X-ray diffraction analysis. Isostructural 5 and 6 crystallise in the triclinic P1¯ (5) and in the monoclinic space group P21/n (6). The two MII(tmeda) entities of 5 and 6 with MII=Ni, Co, respectively, are syn, syn-bridged by two FcCO2− functionalities and one µ-bridging water molecule. Additionally, two FcCO2− ligands are κO-coordinated to each MII ion to form octahedral MN2O4 coordination setups. A related MN2O4 coordination setup is observed for 7 as well, whereby the CuII ion is coordinated by two O2CFc and one tmeda ligand. Electrochemical investigations reveal that all individual Fc units of 5-7 are oxidized separately. Thermogravimetric analysis showed that 5 and 6 start to decompose at 110 and 125°C and thus at significantly lower temperatures compared to 7 (200°C). The mass residues obtained after decomposition are composed of Fe2O3, FeNi3 and Fe0.64Ni=Ni0.36 (5), Fe and Co3O4 (6) and Cu2O and CuFeO2 (7), as determined by powder X-ray diffraction analysis (PXRD). Thermal susceptibility measurements of 5 and 6 determined a weak antiferromagnetic coupling in 5 and 6 with J=1.1K and J=1.9K, respectively.